Protocol of Randomized Controlled Community Trial (RCCT) for obesity management in Brazilian primary health care - Patrícia Pinheiro de Freitas; Mariana Souza Lopes; Jessica Rasquim Araujo; Roberta Brandão da Cunha; Camila Kümmel Duarte; Aline Cristine Souza Lopes (BMC, 2024)
Abstract Background Obesity is a chronic disease characterized by excess body fat and is a risk factor for other chronic non-communicable diseases. Its multifactorial and complex nature makes its management a challenge for health services. This manuscript presents an investigation protocol that aims to analyze the effectiveness of collective nutritional interventions for obesity management applicable to primary health care. Methods Randomized Controlled Community Trial (RCCT) in a representative sample of users of the Programa Academia de Saúde (PAS), in Belo Horizonte, Minas Gerais, Brazil, with obesity. The research consists of four phases: (1) Screening to identify the participants eligible for the nutritional interventions (individuals with obesity, readiness for change to lose body weight, and willingness and interest to participate in a group activity for six months or more); (2) Baseline to characterize the participants; (3) Implementation of collective nutritional interventions; (4) Reassessment of the participants. Participants in the control group (CG) will receive the usual health service care, and participants in the intervention group (IG) will participate in collective nutritional interventions based on Therapeutic Group 1 (TG1) or Therapeutic Group 2 (TG2) of the "Instructive of Collective Approach for the obesity management in SUS". Discussion The strengths of the study include its robust RCCT design, which allows for longitudinal analyses and is suitable for investigating causal hypotheses and applying strategies to improve adherence to interventions. Furthermore, the study included a representative sample of a public health service and aims to evaluate therapeutic proposals from the Brazilian Ministry of Health, which can contribute to implementation and extension in the national territory. Trial registration RBR-3vzsyqq and RBR-6pg682m.